Union of the Comoros : Selected Issues and Statistical Appendix. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2009)
The Selected Issues paper for the Union of the Comoros describes an assessment of the external competitiveness. Comoros has been hard hit by negative terms-of-trade shocks that have weakened the external position. A trend decline in the world price of vanilla, its main export, has occurred parallel to unprecedented increases in international food and petroleum prices. Although export growth has slackened, imports have steadily grown driven by a surge in remittances and a steady real appreciation of the euro-pegged national currency.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet